Statin use during intensive care unit stay is associated with improved clinical outcomes in critically ill patients with sepsis: a cohort study - Li, Caifeng; Zhao, Ke; Ren, Qian; Chen, Lin; Zhang, Ying; Wang, Guolin; Xie, Keliang (Frontiers in Immunology, 2025)
BackgroundDespite early goal-directed therapy, sepsis mortality remains high. Statins exhibit pleiotropic effects, including anti-inflammatory and antimicrobial properties, which may be beneficial during sepsis.ObjectiveTo determine whether statins could improve the clinical outcomes in patients with sepsis.MethodsWe conducted a retrospective cohort study using data from the Medical Information Mart in Intensive Care-IV (MIMIC-IV) database. Adult patients with sepsis were included in the analysis. The exposure factor of this study was statin use during the Intensive Care Unit (ICU) stay. The primary outcome was 28-day all-cause mortality. The secondary outcomes were ICU and in-hospital mortality, length of ICU stay and hospital stay, duration of mechanical ventilation (MV) and continuous renal replacement therapy (CRRT). Both propensity score matching (PSM) and stepwise regression analyses were employed to adjust for potential confounders.ResultsThe unmatched cohort comprised 20230 eligible patients, with 8972 patients in the statin group and 11258 in the no statin group. Propensity score matching generated balanced cohorts with 6070 patients in each group. Post-PSM analysis revealed significantly lower 28-day all-cause mortality in the statin group (14.3% [870/6070]) compared to the no statin group (23.4% [1421/6070]). Statin use was associated with decreased 28-day all-cause mortality (hazard ratio [HR], 0.56; 95% confidence interval [CI], 0.52-0.61; p < 0.001). In subgroup analysis, this beneficial effect was consistent across the different baseline characteristics of patients. Additionally, statin use was associated with decreased ICU mortality (odds ratio [OR], 0.43; 95% CI, 0.37-0.49; p < 0.001) and reduced in-hospital mortality (OR, 0.50; 95% CI, 0.45-0.57; p < 0.001). Sensitivity analysis using the unmatched cohort also showed a significant difference in 28-day all-cause mortality between the statin group and the no statin group (HR, 0.56; 95% CI, 0.52-0.61; p < 0.001).ConclusionStatins were associated with decreased mortality in critically ill patients with sepsis. Further high-quality prospective studies are still needed to verify our findings.